ANALISIS PENDAPATAN USAHA PRODUK NIRA DI DESA LOLAH KECAMATAN TOMBARIRI TIMUR - Mersya Thesalonika Terok; O. Esry H. Laoh; Benu Olfie L. S (AGRI-SOSIOEKONOMI, 2017)
The purpose of this research is to know the total income of sap frompalm sugar (nira) product is income from brown sugar processing and traditional beverage (captikus) in Lolah Village, East Tombariri Subdistrict, Minahasa Regency. This research was conducted for two months, from June to July 2017. The data used are primary data obtained through interviews to 20 entrepreneurs of palm sugar consisting of 2 brown sugar businessmen and 18 traditional beverage(captikus) entrepreneurs and secondary data obtained from Lolah Village Office. The analysis used is income analysis. The results showed that the production of palm juice in Lolah Village was processed into brown sugar and captikus with average monthly income from brown sugar business Rp.2.724.446 and from captikus production amounted to Rp.3.572.751. The total income per month of the production of sap from palm sugar can be obtained by adding the income of brown sugar and captikus which is Rp.6.297.197.-